Does richness of emergent plants affect CO2 and CH4 emissions in experimental wetlands?. (13th April 2015) - Mo, Yi; Deng, Zhao‐Heng; Gao, Jun‐Qin; Guo, Yu‐Xi; Yu, Fei‐Hai
Summary Plant species richness may affect greenhouse gas emissions because it may change ecosystem productivity. Emergent plants are an important component of wetland ecosystems, but little is known about how emergent plant richness affects greenhouse gas emissions. We assembled experimental communities consisting of 1, 2, 4 or 8 emergent plant species in aquatic microcosms and measured community biomass and emissions of CO2 and CH4. Emergent plant richness had little effect on cumulative emissions of CO2 or CH4, most likely because it did not affect community biomass. This conclusion is supported by the fact that CO2 emission was significantly positively related to community biomass. The reason for the unresponsiveness of community biomass to species richness of emergent plants may be that all the plants are in the same functional group so that complementarity among species is weak. CH4 emissions from monocultures of different species differed greatly. Our results do not support the hypothesis that richness of emergent plants plays an important role in regulating greenhouse gas emissions from wetlands. A significant richness effect on greenhouse gas emissions might be detected in wetlands consisting of different plant functional groups such as emergent, floating and submerged plants.